UPAYA MENINGKATKAN MOTIVASI SISWA DALAM PROSES BELAJAR MUSIK REKORDER DI SMP NEGERI 2 KAPUR IX KABUPATEN LIMAPULUH KOTA - Five Alnisa Putra; Syahrel Syahrel; Yos Sudarman (FBS Universitas Negeri Padang, 2017)
AbstractThis research aims to describe students’ motivation in recorder music learning process and the increasing learning activity in recorder music learning process in SMP Negeri 2 Kapur IX. The design of this research was qualitative-descriptive analysis. Research object was seventh grade students at SMP Negeri 2 Kapur IX. The number of students was 32 students. The data was collected by using interview, observation, library research and photograph. The result showed that applying demonstration method in learning ensemble music could increase the learning activity in seven grade SMP Negeri 2 Kapur IX. Based on lesson plan which already arranged and applied in learning process. There were six meetings. Researcher got result 1) Paying attention on teachers’ explanation increased from 70% to 74%. 2) Note-taking activity had significant increased from 60% to 92%. 3) Self-practice activity also increased from 48% to 81%. 4) Musical note reading activity also had significant increased fro 29% to 70%.Key words: motivation, activity, learning process